The Impact of Regional Industrial Structure Upgrading on the Economic Growth of Marine Fisheries in China—The Perspective of Industrial Structure Advancement and Rationalization - Wang, Bo; Han, Limin; Zhang, Hongzhi (Frontiers in Marine Science, 2021)
From the perspective of industrial structure advancement and rationalization, this paper studied the impact of regional industrial structure upgrading on the economic growth of marine fisheries through theoretical analysis and empirical tests. The results show the effects of different industrial structure upgrading on the economic growth of marine fisheries is varied. The advancement evolution has a "suppression effect", while rationalization evolution has a "promotion effect." The adverse impact of advancement evolution is greater than the favorable impact of rationalization evolution. Therefore, the marine fisheries development reduces this unfavorable impact from advancement evolution by accelerating the transformation of innovation-driven internal combustion, and creating new kinetic energy and fostering new business forms; it is also necessary to coordinate regional structure upgrading and industrial internal structure adjustment, promote the effect of structural rationalization, strengthen internal and external linkages, and improve the overall effectiveness of marine fisheries.